The Effect of Social Media Marketing Activities on Brand Loyalty Mediated by Brand Trust and Perceived Value - Ahmada, Anindita Salasa; Prabandari, Sri Palupi; Ismail, Taufiq (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the era of digital marketing, social media has become a crucial platform for companies to engage with customers and influence their purchasing behavior. This study uses the Stimulus-Organism-Response theory to examine the direct effect of social media marketing activities, brand trust, and perceived value on brand loyalty and the mediating roles of brand trust and perceived value. This study used a quantitative explanatory method with 250 samples through purposive sampling, analyzed using SEM-PLS 4.0. The testing covers the outer model, inner model, as well as hypothesis and mediation tests. The results show that social media marketing activities do not directly affect brand loyalty, but they do affect brand trust and perceived value. Brand trust and perceived value have been proven to influence brand loyalty. In addition, both also mediate the relationship between social media marketing activities and brand loyalty. These findings imply that companies should prioritize building trust and enhancing perceived value when designing social media campaigns. Strengthening these factors can lead to higher brand loyalty among customers.